THE NECESSITY OF USING DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF ENGINEERING DEPARTMENTS - Nurov O'tkir Khudoyberdiyevich (American Journals, 2024)
This article discusses the problems of digitalization of engineering education in higher technical educational institutions. The problems of the educational process of engineering disciplines in accordance with the requirements of the era in the conditions of digital technologies are considered.In addition, the possibility of such an educational structure in the process of preparing future engineers for professional activity in the direction of technological processes and machines is considered, which will help to effectively use the interdisciplinary interaction of the curriculum, to find optimal connections between its specific professionally oriented and information components.
Keywords: Higher technical educational institutions, future engineers, professional activity, digital technologies, digitalization, information society, etc.